2021
DOI: 10.17691/stm2021.13.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy in Head and Neck Cancer Treatment: State of the Problem and Development Prospects (Review)

Abstract: Proton therapy (PT) due to dosimetric characteristics (Bragg peak formation, sharp dose slowdown) is currently one of the most hightech techniques of radiation therapy exceeding the standards of photon methods.In recent decades, PT has traditionally been used, primarily, for head and neck cancers (HNC) including skull base tumors. Regardless of the fact that recently PT application area has significantly expanded, HNC still remain a leading indication for proton radiation since PT's physic-dosimetric and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…PT is a generally accepted irradiation method that allows significant reduction of the dose to surrounding tissues, especially relevant for head-and-neck tumors ( 20 ). However, its use is limited by complexity, big size and high costs of the equipment.…”
Section: Discussionmentioning
confidence: 99%
“…PT is a generally accepted irradiation method that allows significant reduction of the dose to surrounding tissues, especially relevant for head-and-neck tumors ( 20 ). However, its use is limited by complexity, big size and high costs of the equipment.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression has been associated with poor response to chemoradiotherapy and poor prognosis in patients with HNSCC [ 96 ], as well as radiation resistance and chronic post-irradiation toxicity development [ 99 ]. These findings identify PT as a highly promising approach in HNSCC treatment, as the conventional photonic options have already reached their technical limits [ 38 , 100 , 101 ].…”
Section: Local and Systemic Effects Of Proton Irradiationmentioning
confidence: 99%
“…Intensity-modulated proton therapy (IMPT) is a promising alternative to conventional photon-based IMRT. Proton therapy (PT) offers advantages over XRT because it can deliver an optimal radiation dose with precision to tumors while sparing the surrounding normal tissues, thus resulting in less treatment-related toxicity with comparable treatment response and disease-free survival [ 3 , 6 , 7 ]. However, a knowledge gap exists not only in the presumed biological advantage of PT over XRT, but also in the molecular and cellular effects of PT on anti-tumor immune responses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PT induces a markedly variable and favorable biological response in terms of gene and protein expression in target tissues compared to XRT. PT inhibits factors that contribute to angiogenesis, inflammation, and DNA damage and favors tumor development and growth, while XRT increases these factors [ 3 , 6 , 8 , 12 , 13 ]. Furthermore, transcriptomic studies in murine models of colon cancer have shown that PT activates anti-tumor immune response pathways [ 9 ].…”
Section: Introductionmentioning
confidence: 99%